Mediações e significações do mundo rural e a Educação do Campo - Brum, Andréia Barreto do Nascimento (2013)
The Field Education is being gradually inserted, in the context of field schools, mainly after Resolutions CNE/CEB Nº1 from 2002 and MEC Nº2 from 2008, aiming treatment of new ruralities of contemporary world and respect for the ways of rural live in every territory. Against the difficulties faced by educational dynamics from the schools to contemplate the wishes, the motivations and interests of general students, including the main goal of this project is the understanding of the significance and mediations of the rural and Field Education inside schools of rural zone o São Sepé city. This research was a qualitative approach with phenomenology as method. Initially it was held a literature review about theories which could collaborate to achieve the goals of this project, later it was held the collection of primary and secondary sources which served as researching tools, analyzed with descriptive and comprehensive focus. The categories of analysis were school and community, as references for the perception of and existing mediations and significance in the stipulated context as field of study of this dissertation. The achieved results showed some difficulties of the field school for its mediations and significances, expressed mainly through pedagogical pratices, are appropriated in positive way by subjects of rural world. It can be concluded that Field Education still needs to be highlighted, as much by keepers of teaching webs as by subjects involved in the educational dynamic of field schools, as a proposal aimed at social, cultural political and economic necessities and its particularities.